Associations of blood mercury, inorganic mercury, methyl mercury and bisphenol A with dental surface restorations in the U.S. population, NHANES 2003–2004 and 2010–2012 - Yin, Lei; Yu, Kevin; Lin, Simon; Song, Xiao; Yu, Xiaozhong (Ecotoxicology and environmental safety, 2016)
The potential adverse health effects of mercury from amalgam and bisphenol A (BPA) from composite resin have been significant concerns. It is unclear whether dental restorative materials significantly contribute to mercury or BPA levels. The purpose of this study is to use NHANES data including 14,703 subjects (2003–2004: n=7514; 2011–2012: n=7189) to examine the association between Dental Surface Restorations (DSR) and blood total mercury (THg), inorganic mercury (IHg), methyl mercury (MeHg) and urinary BPA through the stratification of covariates and multivariate analysis. Subjects were divided into three groups based on the number of dental surface restorations (DSRs, 0, 1–8, >8). Blood THg and IHg in 2003–2004 were significantly higher in the subjects with DSR (geometric mean of 0.48, 0.69 and 1.17μg/l for THg; 0.32, 0.33 and 0.39μg/l for IHg with DSR 0, 1–8 and >8). Similarly, increases of THg, IHg and MeHg were also observed in 2013–2014 (geometric mean of 0.51, 0.69 and 0.99μg/l for THg; 0.40, 0.49 and 0.66μg/l for MeHg; 0.20, 0.22 and 0.29μg/l for IHg with DSR 0, 1–8 and >8). Linear regression model analysis revealed blood THg and IHg in 2003–2004 and THg, IHg and MeHg in 2011–2012 were quantitatively associated with the number of DSRs. A dramatic decrease in urinary BPA from 2003 to 2004–2011–2012 was observed, but no significant increase with DSRs in either period of study. In conclusion, significant increases in blood THg, IHg, and MeHg in the subjects with DSRs are confirmed in a nationally representative population, a critical step in assessing the potential risk of adverse effects from dental restorative materials, but no association between dental fillings and urinary BPA was found. [Display omitted] •Dental filling and blood mercury, and urinary bisphenol A were examined in NHANES.•Total mercury and its species were quantitatively associated with dental fillings.•No association between the dental fillings and urinary BPA was found.